Perfect - Amato, Max (New York : Scholastic Press, 2019)
A fussy eraser tries to keep the pages perfectly clean despite the scribbles of a mischievous pencil.
Keywords: Erasers -- Juvenile fiction; Pencils -- Juvenile fiction; Writing materials and instruments -- Juvenile fiction; Erasers -- Fiction; Pencils -- Fiction; Picture books